2014
DOI: 10.1038/ncomms4891
|View full text |Cite
|
Sign up to set email alerts
|

Clathrin light chains are required for the gyrating-clathrin recycling pathway and thereby promote cell migration

Abstract: The clathrin light chain (CLC) subunits participate in several membrane traffic pathways involving both clathrin and actin, through binding the actin-organizing huntingtin-interacting proteins (Hip). However, CLCs are dispensable for clathrin-mediated endocytosis of many cargoes. Here we observe that CLC depletion affects cell migration through Hip binding and reduces surface expression of β1-integrin by interference with recycling following normal endocytosis of inactive β1-integrin. CLC depletion and express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 59 publications
8
59
0
Order By: Relevance
“…In addition to their structural role in stabilizing clathrin triskelia, CLCs share functions in regulating HSC70, the uncoating ATPase, to disassemble clathrin cages (Schmid et al, 1984; Young et al, 2013), and interacting with HIP1 to link CCVs to the actin cytoskeleton (Chen and Brodsky, 2005; Legendre-Guillemin et al, 2005). A recent study showed that CLCs also modulate a gyrating clathrin structure that mediates the rapid recycling of transferrin receptors (TfnRs) and β1-integrin (Majeed et al, 2014) from early endosomes. Identifying CLC isoform-specific functions has been difficult given their apparently random association with triskelia (Kirchhausen et al, 1983) and substoichiometry with CHC in non-neuronal cells (Borner et al, 2012; Girard et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their structural role in stabilizing clathrin triskelia, CLCs share functions in regulating HSC70, the uncoating ATPase, to disassemble clathrin cages (Schmid et al, 1984; Young et al, 2013), and interacting with HIP1 to link CCVs to the actin cytoskeleton (Chen and Brodsky, 2005; Legendre-Guillemin et al, 2005). A recent study showed that CLCs also modulate a gyrating clathrin structure that mediates the rapid recycling of transferrin receptors (TfnRs) and β1-integrin (Majeed et al, 2014) from early endosomes. Identifying CLC isoform-specific functions has been difficult given their apparently random association with triskelia (Kirchhausen et al, 1983) and substoichiometry with CHC in non-neuronal cells (Borner et al, 2012; Girard et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Variations in cargo crowding and local lipid organization affect membrane-bending properties, which in turn require different coat properties for deformation into a vesicle (35). CLCs contribute tensile strength to the clathrin lattice through controlling the rigidity of the hub region of the triskelion (8,9) and, in cells, by recruiting the actin-regulating Hip proteins (2,6,8,15). Thus, CLCs may contribute to uptake of cargoes that pose particular membranebending challenges.…”
Section: Clc Depletion From Cell Lines Establishes Selectivity For DImentioning
confidence: 99%
“…Vertebrates have two CLC isoforms, CLCa and CLCb, encoded by separate genes, CLTA and CLTB (1). Depletion of both isoforms from tissue culture cells by siRNA treatment showed that CLCs are not required for clathrin-mediated uptake of classic CCV cargoes, such as transferrin receptor (TfR), epidermal growth factor receptor, or low-density lipoprotein receptor (2)(3)(4). CLCs were, however, implicated in uptake of three G protein-coupled receptors (GPCRs) (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The potential function of this gene in cholangiocarcinogenesis is not known; until now there are no reports on overexpression of the gene or its protein in ICC. LCTB may play a physiological role in cell migration and may thereby be upregulated during cell invasion [23].…”
Section: Discussionmentioning
confidence: 99%